Implementation and Training of Congregation Data Management Application at GPID Eben Haezer Palu - Dwi Hosanna Bangkalang; Evangs; Nina Setiyawati; Kristoko Dwi Hartomo; Magdalena Ariance Ineke Pakereng (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
Congregation data collection at GPID Eben Haezer is still done manually. This causes a lot of congregation data to be unsynchronized between the written data and the actual data. In addition, it also results in inefficient administrative services to the congregation. The vision of church digitalization also raises its own problems for the church, namely the unpreparedness of the church's human resources (HR) in digital capabilities. This Community Service (PkM) activity is to help and facilitate GPID Eben Haezer in implementing congregation data management applications and mentoring training in the process of adopting technology in church governance. The training activity was attended by 7 church admins and was carried out after the stages of formulating partner needs, adjusting and implementing the application. After the training, the application usability was measured using the System Usability Scale (SUS) and a score of 83 was obtained, indicating that the implemented application was EXCELLENT and ACCEPTABLE.  Keywords: Congregation Data Collection Application; Digital Skills; Training; System Usability Scale